2012
DOI: 10.4238/2012.october.15.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of ITS sequences of Bursaphelenchus xylophilus

Abstract: ABSTRACT. The sequence variation of internal transcribed spacer (ITS) regions of ribosomal DNA has been routinely used for species identification and species-level phylogeny of the pinewood nematode, Bursaphelenchus xylophilus. In this study, the intraspecies ITS genetic diversity of B. xylophilus was evaluated. Three pinewood nematode isolates from the United States, Japan, and Portugal were used for polymerase chain reaction (PCR) ITS region amplification and sequencing. Multiple peaks were observed in seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…However, some intraisolate genetic variability was found among the determined ITS sequences of BfungPt1 isolate, which is in agreement with the intraisolate molecular variability described for B. xylophilus (Cardoso et al 2012), Meloidogyne species (Hugall et al 1999) or non-phytoparasitic nematodes (Blouin 2002). However, some intraisolate genetic variability was found among the determined ITS sequences of BfungPt1 isolate, which is in agreement with the intraisolate molecular variability described for B. xylophilus (Cardoso et al 2012), Meloidogyne species (Hugall et al 1999) or non-phytoparasitic nematodes (Blouin 2002).…”
Section: Discussionsupporting
confidence: 85%
“…However, some intraisolate genetic variability was found among the determined ITS sequences of BfungPt1 isolate, which is in agreement with the intraisolate molecular variability described for B. xylophilus (Cardoso et al 2012), Meloidogyne species (Hugall et al 1999) or non-phytoparasitic nematodes (Blouin 2002). However, some intraisolate genetic variability was found among the determined ITS sequences of BfungPt1 isolate, which is in agreement with the intraisolate molecular variability described for B. xylophilus (Cardoso et al 2012), Meloidogyne species (Hugall et al 1999) or non-phytoparasitic nematodes (Blouin 2002).…”
Section: Discussionsupporting
confidence: 85%
“…Cardoso et al . () observed that, in B. xylophilus , the ITS diversity was higher in the North American isolates (i.e. from the area of origin of this species) than in Japanese and Portuguese isolates (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Also, this region has shown high polymorphism between B. xylophilus and B. mucronatus populations, both inter-and intra-specific (Futai & Kanzaki, 2002;Cardoso et al, 2012). Likewise, De Luca et al (2011) reported high variability in populations of Pratylenchus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Both regions are used since they provide a valuable tool in the identification of nematodes (PalomaresRius et al, 2010(PalomaresRius et al, , 2013 and reconstruction of phylogenetic relationships (Kaplan et al, 2000;Ye et al, 2007;Coomans et al, 2012). Although molecular studies for identification of B. xylophilus are abundant (Cao et al, 2005;Zhou et al, 2007;Jung et al, 2010;Cardoso et al, 2012;Valadas et al, 2013;Ye & Giblin-Davis, 2013), little is known about B. cocophilus. To date, only four sequences (SSU, LSU and mtCOI regions) of B. cocophilus collected in Costa Rica (one isolate) and Honduras (one isolate) from coconut and African oil palm are available in the NCBI database (Ye et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation